Silk Fiber Films for the Slow and Continuous Release of Tetracycline and Doxycycline - Foroutanjazi, Sadaf. (2018)
Abstract: Aim: To assess the potential use of silk-based films for the slow and continuous release of tetracycline and doxycycline for use in periodontal or other surgical procedures. Hypothesis: We hypothesize that silk-based films will allow for long-term release of antibiotics. Material and Method: Tetracycline and doxycycline were mixed, at various concentrations, with the silk solution. Antibiotic loaded silk fiber films were incubated with Streptococcus mutans cultures to assess the release of the antibiotics. Chlorhexidine was used as a positive control and plain silk films without antibiotic as a negative control. Bacterial growth inhibition was measured spectrophotometrically after each consecutive 24-hour incubation period. The number of colony forming units (CFUs) was determined to validate growth inhibition. Results: Tetracycline and doxycycline-loaded silk fiber films inhibited S. mutans growth in a concentration and time-dependent manner. Tetracycline with the concentrations of 0.375, 0.75 and 1.5 mg/mL inhibited S. mutans growth with noticeable release up to three, four and five days, respectively. Doxycycline with the concentrations of 0.375, 0.75 and 1.5 mg/mL inhibited S. mutans growth up to six, ten and eleven days, respectively. The colony forming units for the 1.5 mg/mL doxycycline and tetracycline exposed S. mutans cultures were 1.2x106 and 1.8x106 CFUs/mL, respectively, which are markedly less compared to the uninhibited control cultures which contained 3.5x109 CFUs/mL. Conclusions: We concluded that tetracycline and doxycycline can be successfully loaded into silk fiber films and inhibited bacterial growth with significant release up to five days for tetracycline and eleven days for doxycycline. Our data implies that silk fiber loaded films can be used as a medium for the localized delivery of antibiotics during periodontal and oral surgeries.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Dental Medicine.; Advisor: Driss Zoukhri.; Committee: Gerard Kugel, Tofool Alghanem, Sarah E. Pagni, and Aidee N. Herman.; Keyword: Dentistry.